A new order, Entrophosporales, and three new Entrophospora species in Glomeromycota - Błaszkowski, Janusz; Sánchez-García, Marisol; Niezgoda, Piotr; Zubek, Szymon; Fernández, Félix; Vila, Ana; Al-Yahya’ei, Mohamed N.; Symanczik, Sarah; Milczarski, Paweł; Malinowski, Ryszard; Cabello, Marta; Goto, Bruno Tomio; et al. (Frontiers in Microbiology, 2022)
As a result of phylogenomic, phylogenetic, and morphological analyses of members of the genus Claroideoglomus, four potentially new glomoid spore-producing species, and Entrophospora infrequens, a new order, Entrophosporales, with one family, Entrophosporaceae (= Claroideoglomeraceae), was erected in the phylum Glomeromycota. The phylogenomic analyses recovered the Entrophosporales as sister to a clade formed by Diversisporales and Glomeraceae. The strongly conserved entrophosporoid morph of E. infrequens, provided with a newly designated epitype, was shown to represent a group of cryptic species with the potential to produce different glomoid morphs. Of the four potentially new species, three enriched the Entrophosporales as new Entrophospora species: E. argentinensis, E. glacialis, and E. furrazolae, which originated from Argentina, Sweden, Oman, and Poland. The fourth fungus appeared to be a glomoid morph of the E. infrequens epitype. The physical association of the E. infrequens entrophosporoid and glomoid morphs was reported and illustrated here for the first time. The phylogenetic analyses, using nuc rDNA and rpb1 concatenated sequences, confirmed the previous conclusion that the genus Albahypha in the family Entrophosporaceae sensu Oehl et al. is an unsupported taxon. Finally, the descriptions of the Glomerales, Entrophosporaceae, and Entrophospora were emended and new nomenclatural combinations were introduced.